Does an integrated, wrap-around school and community service model in an early learning setting improve academic outcomes for children from low socioeconomic backgrounds? - Newman, S; McLoughlin, J; Skouteris, H; Blewitt, C; Melhuish, E; Bailey, C (Taylor and Francis, 2020)
Many children start school developmentally vulnerable and struggle to keep up with their peers. Children experiencing socioeconomic-disadvantage are at higher risk of poor developmental outcomes. A high-quality education and wrap-around community-service model, such as the Doveton Model, at Doveton College, Australia, may improve outcomes for families experiencing entrenched disadvantage. This study focussed on the effect of this model on early-learning (pre-formal schooling) for school entry readiness and academic achievement over the subsequent four years. Students who did/did not attend the Doveton Model Early-Learning-Centre were compared using standard reading, oral-language, writing and numeracy tests from school-entry to Year 3. There was a trend towards higher academic achievement for students who attended Doveton early-learning compared to students who had not. Many tests showed statistically significant differences, despite low sample sizes. This study provides preliminary evidence that attending early-learning within a high-quality, wrap-around service model may have significant academic benefits for disadvantaged children.